Effect of an experimental dentin conditioner on micro-tensile bond strength of 4-META/MMA-TBB resin to dentin after long-term water immersion - TAIRA, Yohsuke; ATSUTA, Mitsuru; SOENO, Kohyoh (Adhesive Dentistry, 2007)
The current study investigated the effect of an experimental dentin conditioner on the bond strength of 4-META/MMA-TBB resin to dentin after long-term immersion in water. The experimental conditioner (AS-FE) was an aqueous solution of 10 wt% ascorbic acid and 5 wt% ferric chloride. Human molar teeth were prepared to expose flat dentin surfaces. The dentin was treated sequentially with 40 wt% phosphoric acid, 10 wt% NaClO and the AS-FE (Exp). A commercially available dentin conditioner, an aqueous solution of 10 wt% citric acid with 3 wt% ferric chloride, was used as a control group (10-3). The pretreated dentin surfaces were bonded to resin rods using the 4-META/MMA-TBB resin. Micro-tensile bond strengths were determined after water immersion for 24 hours, 12 months, 18 months, 24 months, and 30months. All data were analyzed by ANOVA, and differences among groups were analyzed by Duncan's new multiple range test (n=13, p<0.05). Mean bond strength of Exp was significantly higher than that of the 10-3 through water immersion for 30 months. Exp also showed no significant decrease through water immersion for 30 months, while 10-3 exhibited a significant decrease after water immersion for 12-30 months compared to that for 24 hours. The present findings suggested that the use of the AS-FE conditioner in conjunct with phosphoric acid and NaClO improved the bonding durability between 4-META/MMATBB resin and human dentin.